Successful balloon valvuloplasty of rheumatic mitral valve stenosis in a pregnant patient without fluoroscopy: a case report. Issue 2 (16th May 2018) - Ubben, Timm; Frerker, Christian; Kuck, Karl-Heinz; Schmidt, Tobias
Abstract: Introduction: Rheumatic mitral stenosis (MS) is the most common rheumatic heart disease that complicates pregnancy. Percutaneous transvenous mitral commissurotomy (PTMC) has become the first-choice treatment, but is routinely performed with fluoroscopic guidance, which bears risks from ionizing radiation for the embryo when performed in pregnant patients. Case presentation: A pregnant patient was referred to our department for therapy of severe MS after she suffered from cerebral artery infarction. The patient underwent successful PTMC under exclusive echocardiographic imaging and showed stable results throughout the pregnancy. The patient showed an improvement in functional capacity from dyspnoea New York Heart Association (NYHA) III to I and delivered a healthy child without any complications. Discussion: This case shows that PTMC of MS under exclusive echocardiography guidance without fluoroscopy is feasible and appears to be safe without causing radiation damage to the embryo.